ANALISIS KELEMBAGAAN DALAM PELAKSANAAN PROGRAM HUTAN KEMASYARAKATAN DI DESA GETAS, KECAMATAN PLAYEN, KABUPATEN GUNUNGKIDUL - , MARIA DEWI PERMATASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Forest degradation which is not equal to the forest improvement effort is now getting damaged. Besides, the low economic conditions have affected people's behavior in dealing with natural resources. Program Hutan Kemasyarakatan (HKm) or Community Forest Programme aims to conserve forests and improve the welfare of the society. Institution is one of the important elements in supporting the successful implementation of social forest. This study aims to determine the institutional system in social forest management, institutional dynamics of forest farmer groups, and the problems faced by institution and the alternative solutions. This research was conducted in Gubugrubuh Hamlet, Getas Village, Playen Subdistrict, Gunungkidul Regency, pcecisely at pot 74 which is reserved for the production of forest community for social forestry. This study uses a quantitative approach with a survey method. The collecting of data is done by direct observation, interviews and document research. The technique of collecting sample is done by using purposive sampling